Verbs in Hindi: A semantico-syntactic classification - Richa, Richa (Journal of Modern Languages, 2017)
Hindi, an Indo-Aryan language has the vocabulary of mostly tatsam (borrowed from Sanskrit and kept intact) and tadbhav (derived from Sanskrit and modified) words. The examination of the root forms shows that most of the verbs are intransitive at base but the present paper argues that morphology cannot be the reliable basis to decide this. Hence, the need of the hour is to probe into their semantico-syntactic behaviour and classify them according to that criterion. The paper provides a detailed semantic-syntactic classification of Hindi verbs. This classification will also provide a range of information regarding the linguistic properties of the verbs. It will be a powerful resource for various NLP applications as well as research in the area of cognitive linguistics.